Can Asymptomatic or Non-Severe SARS-CoV-2 Infection Cause Medium-Term Pulmonary Sequelae in Children? - Bottino, Ilaria; Patria, Maria F.; Milani, Gregorio P.; Agostoni, Carlo; Marchisio, Paola; Lelii, Mara; Alberzoni, Marco; Dell'Era, Laura; Castellazzi, Massimo L.; Senatore, Laura; Madini, Barbara; Pensabene, Maria C.; et al. (Frontiers in Pediatrics, 2021)
Pulmonary complications in adults recovered by Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV-2) have been reported even in minimally symptomatic patients. In this study, evaluated lung ultrasound findings and pulmonary function of children who recovered from an asymptomatic or mildly symptomatic SARS-CoV-2 infection were evaluated. We prospectively followed-up for at least 30 days, patients younger than 18 years, recovered from SARS-CoV-2 infection at the Fondazione IRCCS Ca’ Granda Ospedale Maggiore Policlinico, Milan (Italy). All enrolled patients underwent lung ultrasound (LUS). Airway resistance measured by the interrupter technique test was assessed in subjects aged 4-6 years, whereas forced spirometry and measurement of diffusing capacity of the lungs for carbon monoxide were performed in subjects older than 6 years. To evaluate a possible correlation between pulmonary alterations and immune response to SARS-CoV-2, two semiquantitative enzyme immune assays were used. We enrolled 16 out of 23 eligible children. The median age of enrolled subjects was 7.5 [0.5-10.5] years, with a male to female ratio of 1.7. No subject presented any abnormality on LUS, airway resistance test, forced spirometry, and diffusing capacity of the lungs for carbon monoxide. On the other hand, all subjects presented Ig G against SARS-CoV-2. In contrast with adults, we did not detect any pulmonary complications in our cohort. These preliminary observations suggest that children with an asymptomatic or mildly symptomatic SARS-CoV-2 infection might be less prone to develop pulmonary complications than adults.